Introducing and Exploring the Extremist Cybercrime Database (ECCD) - Holt, Thomas J. (Crime & delinquency, 2023)
This study uses open source, public information to examine nation-state and non-nation-state ideologically motivated cyberattacks performed against US targets from 1998 to 2018. We created the Extremist Cyber Crime Database (ECCD) that includes scheme, offender and target codebooks to address gaps in existing research and better inform policymakers. We describe our open source collection procedures, the type of information uncovered, and how we assessed their quality and reliability. We highlight our findings, compare these extremist cyber-crimes to extremist real world violence, and discuss their conceptual and policy implications.